Factors Associated with Survival of Veterans with Gastrointestinal Neuroendocrine Tumors. (27th May 2012) - Balmadrid, Bryan L.; Thomas, Catherine M.; Coffman, Cynthia J.; Liddle, Rodger A.; Fisher, Deborah A.
Abstract : Background . Gastrointestinal (GI) neuroendocrine tumor (NET) incidence has been increasing; however, GI NET within the national Veterans Affairs (VA) health system has not been described. Methods . We used the VA Central Cancer Registry to identify the cohort of patients diagnosed with GI NET in 1995–2009. Cox regression models were constructed to explore factors associated with survival. Results . We included 1793 patients with NET of the stomach (9%), duodenum (10%), small intestine (24%), colon (19%) or rectum (38%). Twenty percent were diagnosed in 1995–1999, 35% in 2000–2004, and 45% in 2005–2009. Unadjusted 5-year survival rates were: stomach 56%, duodenum 66%, small intestine 52%, colon 67%, and rectum 84%. Factors associated with shorter survival were increasing age, hazard ratio (HR) 1.05 (95% CI 1.04–1.06), NET location [compared to rectum: stomach HR 2.26 (95% CI 1.68–3.05), duodenum HR 1.70 (95% CI 1.26–2.28), small intestine HR 1.85 (95% CI 1.42–2.42), and colon 1.83 (95% CI 1.41–2.39)], stage [compared to in situ /local: regional HR 1.15 (95% CI 0.90–1.47), distant HR 2.38 (95% CI 1.87–3.05)], and earlier period of diagnosis [compared to 1995–1999: 2000–2004 HR 0.70 (95% CI 0.59–0.85), 2005–2009 HR 0.43 (95% CI 0.34–0.54)]. Conclusions . The incidence of GI NET has also increased over time in the VA system with similar survival rates to those observed in non-VA settings. Worsened survival was associated with older age, tumor site, advanced stage, and earlier year of diagnosis.